2017
DOI: 10.1515/vjbsd-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Price Transmission of Milk Prices Among the Visegrad Countries

Abstract: When trading with homogenous goods, consumers are not able to distinguish between individual goods and thus not willing to pay a higher price, if the same product is available for lower price. This leads to an interesting effect, when prices of homogenous goods in different locations in an open market tend to get closer. It is the result of the so-called Law of One Price. Because of the Law of One Price, producers are affected not only by vertical price transmission, but also horizontally. The aim of this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…The milk quota system was applied from 1984 to 2015 by the European Union (EU), as a tool to control the milk production [24]. It is considered one of the main efficient systems that was employed to regulate the milk markets of all EU members [25], especially after creating financial problems due to the excess production of butter and milk powder [1]. After the abolition of the milk quota in 2015, the Hungarian milk sector witnessed a difficult situation.…”
Section: The Dairy Sector In Hungarymentioning
confidence: 99%
“…The milk quota system was applied from 1984 to 2015 by the European Union (EU), as a tool to control the milk production [24]. It is considered one of the main efficient systems that was employed to regulate the milk markets of all EU members [25], especially after creating financial problems due to the excess production of butter and milk powder [1]. After the abolition of the milk quota in 2015, the Hungarian milk sector witnessed a difficult situation.…”
Section: The Dairy Sector In Hungarymentioning
confidence: 99%
“…Their results show that the US and New Zealand are the main dairy markets and the shocks on these markets spread out across the world. Vargova and Rajcaniova (2017) analyzed the spatial price transmission between milk markets in Hungary, Poland, Slovakia and Czech Republic. They found that the prices between these four countries are cointegrated, and they confirmed the existence of the LOP in these markets.…”
Section: Literature Reviewmentioning
confidence: 99%